An Industrial Quality Control Study on Noritake Porcelana Manufacturing, Inc. - Agno, Kristine Lufel Y.; Juadiong, Michael Robert M.; Torres, Richelle D. (Diliman, Quezon City College of Engineering, 2006)
The quality control study on Noritake Porcelana Manufacturing, Inc. aims to apply the basic concepts and principles of Statistical Quality Control to evaluate the company's current quality control system. Specifically, the study aims to determine the most common defects found in the final product, to identify the areas in the manufacturing process which would require control charts and produce them, and to present recommendations on quality control. The study is limited to the processes from preparation of materials to the production of glostware after firing, and to the New White 7 (NW 7) product line formulation of the chinaware. Defect identification is also based only on the inspections conducted from January to June 2005. Important points in the manufacturing process are identified through dialogues with the Quality Assurance supervisor and Human Resources staff, and control charts are constructed. Given the percentages of each defect, a Pareto chart is constructed and the most common defects are identified; these are the iron spots, poor edge, warp, and pitting. The process proportion defective control chart (P-control chart) shows out-of-control process due to assignable causes such as operator error and improper adjustment of the machines. At present, the company uses 100 percent inspection on the final product but their acceptance sampling method for the firing process does not have a definite sampling plan. The group recommends that the company use Double Sampling Method, Tightened at Acceptable Quality Level (AQL) of 1.0 percent since this method is shown to be the one that matches their current method of inspection. This plan makes use of 125 samples wherein detecting zero or one defective unit out of the 125 samples will sentence the lot as good and detecting nonconforming units greater than 4 will sentence the lot as rejected. However, if the number of nonconforming units is between 1 and 4, this sends the lot to the second random sampling of 125 units. Failure Mode and Effects Analysis shows that in the processes of preparation, forming, biscuit firing, glazing/glost firing, sagger formation, and loading and unloading, the causes of failure are mostly machine-related; few causes of failure are worker-related. Preparation and forming processes contribute in the formation of iron spots; forming process contribute to poor edge; forming and glost firing processes play part in pitting; and preparation and biscuit firing processes play part in rim warp. Machine irregularities such as in ferro filter, vibrating sieve, filter press, pug mill, and sagger refractory can be controlled by proper and regular maintenance and monitoring of these machines. Other defects that are work-related such as cracks can be controlled by proper training, and careful and cautious handling of workers.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Noritake Porcelana Manufacturing Incorporated; Porcelain industry; Quality control